Pathological narcissism mentalization and gender differences in alcohol misuse among emerging adults - Andrea Fontana; Stefano Toselli; Ilaria Maria Antonietta Benzi; Laura Antonia Lucia Parolin; Marco Cacioppo; Nicola Carone (Discover Psychology)
Abstract Background Emerging adulthood is a developmental phase marked by increased vulnerability to risky behaviors, including alcohol misuse. Pathological narcissism, particularly grandiose and vulnerable traits, has been identified as a key factor influencing alcohol misuse. The role of mentalized affectivity (namely, the ability to identify, express, and process emotions) may enhance these associations, along with potential gender differences in these dynamics. Methods A cross-sectional study was conducted with 1,075 emerging adults (M = 24.26, SD = 2.43; 71.2% assigned female at birth), using self-reports to measure pathological narcissism, mentalization difficulties, and alcohol misuse. Hierarchical regression models were used to examine the relationships between narcissistic traits, mentalized affectivity, and alcohol misuse. Results Grandiose narcissism was associated with alcohol misuse in the total sample. Narcissistic vulnerability was a stronger predictor of alcohol misuse in female individuals, while difficulties in mentalization (identifying and expressing emotions) were significant predictors of alcohol misuse in males. Grandiose narcissism did not directly predict alcohol misuse in either gender, after controlling for Narcissistic vulnerability. Conclusions Vulnerable narcissism plays a significant role in alcohol misuse, especially in female individuals, with mentalization difficulties exacerbating these behaviors, particularly in male individuals. Gender differences highlight the need for gender-specific interventions in emerging adults.